2018
DOI: 10.3399/bjgpopen18x101565
|View full text |Cite
|
Sign up to set email alerts
|

Health service use by same-sex attracted Australian women for alcohol and mental health issues: a cross-sectional study

Abstract: BackgroundSame-sex attracted women (SSAW) have higher rates of alcohol and mental health problems than heterosexual women, but utilisation of and satisfaction with treatment is limited.AimThis study investigated the influences on health service use for alcohol and mental health problems among SSAW.Design & settingThe Gelberg-Andersen behavioural model of health service utilisation was used to generate outcome variables.MethodA convenience sample of 521 community-connected Australian SSAW completed an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…One recent study showed that 70% of LGBQ cisgender people indicating clinical levels of distress hadn't accessed mental health care in the past 6 months, and almost one-fifth had never done so despite feeling it would be beneficial (Cronin et al 2021). Similar behaviours have been noted in LBQ+ women populations, in which two-fifths of those participating in a previous study believed they needed mental health or alcohol-related support but had never accessed it (McNair et al 2018).…”
Section: Introductionmentioning
confidence: 76%
“…One recent study showed that 70% of LGBQ cisgender people indicating clinical levels of distress hadn't accessed mental health care in the past 6 months, and almost one-fifth had never done so despite feeling it would be beneficial (Cronin et al 2021). Similar behaviours have been noted in LBQ+ women populations, in which two-fifths of those participating in a previous study believed they needed mental health or alcohol-related support but had never accessed it (McNair et al 2018).…”
Section: Introductionmentioning
confidence: 76%
“…Four studies examined the associations between IPV and physical health (Lehavot et al, 2009; McCauley et al, 2015; Muzny et al, 2018; Oginni et al, 2021). Another three examined healthcare utilization and costs (Coston, 2020; McNair et al, 2018; Valentine et al, 2015). Seven studies tested associations between IPV and mental health (Charak et al, 2019; Coston, 2019; Descamps et al, 2000; Hellemans et al, 2015; Lehavot et al, 2009; Longares et al, 2016; Muzny et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the burdens of increased healthcare needs and costs, the majority of SMW experiencing IPV do appear to seek help. In a convenience sample of same sex-attracted Australian women ( N = 521), 66% of participants who experienced past year IPV received mental health or alcohol treatment (McNair et al, 2018). However, as a group, they may still underutilize resources.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, participants with a regular GP may experience support from their GP to navigate the health system and are consequently more confident that they will be able to access inclusive services. Accordingly, previous Australian research has shown that sexual minority women with a regular GP were more likely to utilise additional healthcare services such as alcohol and mental health support services (McNair et al, 2018).…”
Section: Discussionmentioning
confidence: 99%